Method for separating and quantitatively analyzing two forms of tin in cu-sn02 composite material
Patent Information
- Application Number
- CN202611013786.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-09
AI Technical Summary
一方面,传统ICP全消解分析通常只能获得样品中的总锡含量,无法区分不同形态锡的贡献;另一方面,基于残渣称重的氧化锡测定方法仅依据残渣质量进行计算,缺乏对残渣真实物相组成的验证,难以准确判断残渣是否全部为SnO2
1)本发明通过硝酸选择性溶解、络合稳定处理、微孔过滤分离以及滤液分析和残渣物相验证相结合的技术路线,实现了铜基SnO2复合材料中固溶态锡与氧化态锡的分别测定,解决了现有技术无法准确区分不同形态锡的问题。
Smart Images

Figure CN122882159A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of Cu-SnO2 composite material preparation, and more specifically, to a method for quantitative analysis of the separation of two forms of tin in Cu-SnO2 composite materials. Background Technology
[0002] Cu-Sn alloys are widely used in electrical and electronic engineering, rail transportation, integrated circuit lead frames, and electrical contact materials due to their excellent electrical, thermal, and mechanical properties. In recent years, to further improve the strength, thermal stability, and softening resistance of copper alloys, researchers have gradually adopted techniques such as internal oxidation, powder metallurgy, and oxide dispersion strengthening (ODS) to introduce nano- or micron-sized oxide particles into the copper matrix. Among these, oxide particles, represented by SnO2, have attracted widespread attention in the field of high-strength, high-conductivity copper alloys due to their high thermal stability and good interfacial bonding ability.
[0003] In Cu-SnO2 composite materials, tin typically exists in two different forms: solid-solution tin dissolved in the copper matrix and tin oxide tin in the form of tin oxide particles. These different forms of tin have significantly different effects on material properties. Solid-solution tin can improve material strength through solid solution strengthening, but it also increases electron scattering and reduces conductivity. Tin oxide, existing as SnO2 particles, can improve material strength and thermal stability through dispersion strengthening, while having a relatively small impact on conductivity. Therefore, accurately determining the content and ratio of solid-solution tin and tin oxide in materials is crucial for studying the evolution of material microstructure, establishing composition-microstructure-property relationships, and optimizing preparation processes. Currently, the determination of tin content in copper-based materials mainly employs inductively coupled plasma atomic emission spectrometry (ICP-OES), inductively coupled plasma mass spectrometry (ICP-MS), and gravimetric analysis. In the ICP method, the total tin content is usually determined by completely dissolving the sample with acid. For the determination of tin oxide content, the method often involves selectively dissolving the copper matrix with nitric acid, filtering the residue, and then calculating the tin oxide content based on the mass of the residue.
[0004] For example, Chinese patent CN1501409A (application number 03157594.3, publication date June 2, 2004, applicant Sumitomo Electric Industries, Ltd.) discloses a copper alloy conductor and its manufacturing method. In this patent, to limit the weight ratio of tin component to elemental tin in tin oxide to no more than 0.3, the following determination method is used: A copper alloy conductor sample is dissolved in 60% nitric acid, allowing the copper matrix and elemental tin to dissolve into the solution, while tin oxide (SnO2) precipitates and separates as an insoluble substance. Atomic absorption spectrometry is performed on the clarified portion to determine the mass of dissolved Sn. Emission spectrophotometric analysis is used to determine the total weight of tin. The weight of elemental Sn is then subtracted from the total weight of tin to obtain the weight of tin contained in SnO2.
[0005] However, although the aforementioned patents disclose methods for determining the tin oxide content in copper alloys through nitric acid dissolution and residue analysis, they only focus on the influence of tin oxide content and particle size on material properties. They do not establish a quantitative analysis system for the separation of tin in solid solution and tin in oxide, and cannot obtain the true content and ratio of tin in different forms. At the same time, they lack phase verification methods such as XRD and EDS, and cannot confirm the true composition of the residue. They also do not study the statistical accuracy of tin in oxide during ICP analysis.
[0006] It is evident that existing analytical methods for Cu-SnO2 composites containing both dissolved tin and SnO2 particles have significant limitations. On one hand, traditional ICP total digestion analysis typically only yields the total tin content of the sample, failing to distinguish the contributions of different tin forms. On the other hand, tin oxide determination methods based on residue weighing rely solely on residue mass calculations, lacking verification of the actual phase composition of the residue and making it difficult to accurately determine whether the residue is entirely SnO2. Furthermore, during acid dissolution, filtration, and subsequent processing, different tin forms may migrate, be lost, or undergo distribution changes, leading to deviations in the measurement results.
[0007] In view of this, the present invention is hereby proposed. Summary of the Invention
[0008] The purpose of this application is to provide a method for the separation and quantitative analysis of tin in two forms in Cu-SnO2 composite materials. This method combines selective dissolution of the copper matrix, complexation and stabilization of tin ions in the solution, separation of tin oxide particles by microfiltration, determination of the content of tin in solid solution in the filtrate, and verification of the phase composition of the residue. This method can achieve the separation and quantitative analysis of tin in different forms in the material and therefore has broad application value.
[0009] To achieve the above objectives, this invention provides a method for the quantitative analysis of two morphologies of tin in Cu-SnO2 composite materials, comprising the following steps: After the Cu-SnO2 composite material is fully dissolved in acid, a complexing agent is added and stirred, and then solid-liquid separation is performed using a microporous filter membrane to obtain a filtrate containing solid tin and metal ions dissolved in the solution, as well as a residue containing tin oxide particles. The filtrate was quantitatively analyzed to determine the tin content, and the residue was washed to determine the content of tin oxide. The contents of solid solution tin and tin oxide in Cu-SnO2 composite material were obtained by the above determination.
[0010] In existing technologies, the analysis of tin in copper-based SnO2 composite materials mainly uses methods such as total tin determination or tin oxide content determination. These methods can only obtain the total tin content or tin oxide content in the material, and cannot simultaneously obtain the content and distribution relationship of tin in solid solution and tin oxide. At the same time, existing technologies lack phase composition verification for filter residues, cannot confirm the actual existence state of tin oxide in the residues, and cannot establish a quantitative relationship between tin in solid solution and tin oxide, making it difficult to meet the needs of analyzing different forms of tin in copper-based SnO2 composite materials.
[0011] Therefore, to solve the above-mentioned technical problems, this invention provides a method for the separation and quantitative analysis of tin in solid solution and tin oxide in copper-based SnO2 composite materials, achieving effective separation, separate determination, and quantitative analysis of tin in different forms in the material. This method is applicable to internally oxide Cu-Sn alloys, Cu-SnO2 composite materials, oxide dispersion-strengthened copper alloys, and other copper-based materials containing both solid solution and tin oxide. It achieves the separation and quantitative analysis of tin in different forms by combining a technical route of selectively dissolving the copper matrix, complexing and stabilizing tin ions in the solution, separating tin oxide particles through microporous filtration, determining the content of solid solution tin in the filtrate, and verifying the phase composition of the residue.
[0012] Preferably, as a further feasible option, the acid used for acid dissolution is a 50-68% mass fraction of at least one of nitric acid or other acid systems capable of dissolving the copper matrix while retaining the tin oxide particles, and the mass of the acid added is 3-20 times the mass of the sample.
[0013] Preferably, as a further feasible option, the acid used for dissolution is a 60% nitric acid solution.
[0014] The acid solution used to dissolve the sample in this invention can be nitric acid or other acid systems capable of dissolving the copper matrix while retaining the tin oxide particles. During sample dissolution, either static dissolution at room temperature or assisted heating can be used to ensure complete dissolution of the copper matrix. This allows the copper matrix and the tin dissolved within it to fully enter the solution, while the tin oxide particles remain in the solid residue. Preferably, a nitric acid solution with a mass fraction of 55-65% is used, more preferably a nitric acid solution with a mass fraction of 60%, to balance matrix dissolution efficiency and subsequent analytical stability.
[0015] Preferably, as a further feasible option, the complexing agent is at least one of tartaric acid, citric acid, ethylenediaminetetraacetic acid, or oxalic acid, and the amount of complexing agent added is 0.05-0.2 times the mass of the sample.
[0016] Preferably, as a further feasible option, the complexing agent is tartaric acid, and the amount of the complexing agent added is 0.08-0.12 times the mass of the sample.
[0017] This invention aims to stabilize the state of tin ions in solution by adding a complexing agent. After adding the complexing agent, it is best to continue stirring for 1-10 minutes, preferably 3-5 minutes, to make the system reach a stable state and provide conditions for subsequent solid-liquid separation.
[0018] Among the aforementioned complexing agents, tartaric acid is the best choice because of its high complexing stability. It can effectively complex and stabilize Sn ions, inhibiting hydrolysis and secondary precipitation, and suppressing Sn... 4+ The formation of a pseudo-precipitate of stannic acid makes it the optimal choice. However, care must be taken regarding the dosage; too much dosage may introduce new impurities, while too little will fail to stabilize the ionic state. Therefore, it is best to select the dosage according to the methods described in this invention. The most preferred dosage of the complexing agent is 0.1 times the mass of the sample.
[0019] Preferably, as a further feasible option, the microporous filter membrane is a polyethersulfone filter membrane, a polytetrafluoroethylene filter membrane, or a nylon filter membrane, and the pore size of the microporous filter membrane is 0.10-1.00 μm.
[0020] Preferably, as a further feasible option, the microporous filter membrane is a polyethersulfone filter membrane, and the pore size of the microporous filter membrane is 0.22-0.45 μm. More preferably, the pore size of the microporous filter membrane is 0.45 μm.
[0021] This invention employs a microporous membrane to better achieve solid-liquid separation. The optimal type of microporous membrane is a polyethersulfone (PES) membrane, as it achieves a good balance in terms of material chemistry, physical structure, and application performance. Therefore, this type of microporous membrane can be selected for filtration. After filtration, two parts are obtained: a filtrate and a residue. The filtrate mainly contains dissolved tin and metal ions dissolved in the solution, while the residue mainly retains tin oxide particles.
[0022] Of course, in addition to the above filtration methods, pressure filtration devices or centrifugal separation methods can also be used to achieve solid-liquid separation.
[0023] Preferably, as a further feasible option, the method for determining the tin oxide content after cleaning the residue includes: washing 3-10 times, drying at 80-120℃, recording the mass of the residue, and calculating the corresponding tin oxide content of the residue based on the mass fraction of tin in tin oxide. Preferably, the number of washing cycles is 5, and the drying temperature is preferably 105℃, until a constant weight is achieved. After confirming by XRD and SEM / EDS that the residue is mainly composed of SnO2, the content of tin oxide in the material is obtained by calculating according to the theoretical mass fraction of tin in SnO2.
[0024] When determining the tin content in the filtrate, first bring the volume to 100-1000 mL with deionized water, preferably to 500 mL. Then, determine the tin content in the filtrate using inductively coupled plasma optical emission spectrometry (ICP-OES) or inductively coupled plasma mass spectrometry (ICP-MS), and calculate the dissolved tin content in the sample based on the results. Since this portion of the tin originates from the tin that enters the liquid phase during the nitric acid dissolution process, the results are used to characterize the dissolved tin content in the material.
[0025] Preferably, as a further feasible option, after determining the content of tin oxide in the residue cleaning process, the method further includes a step of confirming the true composition of the residue, specifically including: The residue was examined using an X-ray diffractometer with a scanning range of 10°-90°. The diffraction peaks were compared with those on a standard card to confirm the presence of the SnO2 phase in the residue. The morphological characteristics of the residue particles were observed using a scanning electron microscope, and point and surface scanning analyses were performed using energy dispersive spectroscopy to confirm the distribution of Sn and O elements in the particles.
[0026] The above steps are for more accurate phase and composition analysis of the residue, thereby verifying whether the residue is mainly composed of tin oxide particles. A scanning range of 20°-80° is preferred.
[0027] In liquid phase analysis, in addition to ICP-OES, ICP-MS, atomic absorption spectrometry (AAS), or other analytical methods capable of determining the tin content in the solution can also be used. In residue verification, in addition to XRD and SEM / EDS, electron probe microanalysis (EPMA), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), or other methods capable of characterizing the phase and elemental composition of the residue can also be used.
[0028] Preferably, as a further feasible option, after obtaining the contents of tin in solid solution and tin in oxide in Cu-SnO2 composite material, the method further includes a step of calculating the ratio between tin in oxide and tin in solid solution, with the aim of establishing a quantitative analysis system for tin elements in different forms in Cu-SnO2 composite material.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) This invention achieves the separate determination of solid-solution tin and oxide tin in copper-based SnO2 composite materials by combining selective dissolution with nitric acid, complexation stabilization treatment, microporous filtration separation, filtrate analysis and residue phase verification, thus solving the problem that existing technologies cannot accurately distinguish between different forms of tin.
[0030] 2) This invention verifies the residue using XRD and SEM / EDS, which can confirm the presence state of tin oxide in the residue and improve the reliability of the tin oxide analysis results.
[0031] 3) This invention can simultaneously obtain the content of tin in solid solution, the content of tin in oxide and their ratio, providing a reliable analytical method for the composition analysis and microstructure and property study of Cu-SnO2 composite materials, Cu-Sn alloys with internal oxide and other copper-based materials containing tin oxide.
[0032] Other features and advantages of this application will be described in detail in the following detailed description section. Attached Figure Description
[0033] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0034] Figure 1 This is a schematic flowchart of the method for quantitative analysis of two morphologies of tin in Cu-SnO2 composite material provided in Example 1 of the present invention; Figure 2 The image shows the XRD pattern of the residue in Embodiment 1 of the present invention; Figure 3 This is a SEM+EDS image of the residue in Example 1 of the present invention; Figure 4 This is a SEM+EDS image of the residue in Comparative Example 2 of the present invention. Detailed Implementation
[0035] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are only some embodiments of the present invention, not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0036] Example 1 The method for quantitative analysis of the two forms of tin in Cu-SnO2 composite materials is as follows: Figure 1 As shown: Weigh 28.760 g of Cu-SnO2 composite material sample and place it in a beaker. Add 100 mL of 60% nitric acid solution to dissolve it. After the copper matrix is completely dissolved, immediately add 0.1 times the sample mass of tartaric acid as a complexing agent and stir for 1 min for complexation stabilization treatment. Then filter the sample using a 0.45 μm pore size polyethersulfone membrane and collect the filtrate and filter residue separately.
[0037] After diluting the filtrate to 500 mL, the tin content was determined by ICP-OES, and the calculated solid-solution tin content in the sample was 0.0936 wt.%. The filter residue was washed three times with deionized water and dried at 120 °C to constant weight, yielding a residue mass of 61.45 mg. Based on the theoretical composition of SnO2, the tin oxide content was approximately calculated, with a theoretical tin mass fraction of 78.77%, resulting in an tin oxide content of 0.1683 wt.%. Therefore, the actual measured tin content in the sample was calculated to be 0.2619 wt.%. Due to a small amount of residue loss during filtration and collection, the calculated tin oxide content is slightly lower than the theoretical value.
[0038] To confirm the true composition of the residue, X-ray diffraction (XRD) was used to examine it, with the preferred scanning range being 10°–90°. Figure 2XRD analysis of the filter residue showed that the main diffraction peaks corresponded to the SnO2 standard card. Further scanning electron microscopy (SEM) was used to observe the morphology of the residue particles, and energy dispersive spectroscopy (EDS) was used for point and area scanning analysis to confirm the distribution of Sn and O elements in the particles, thus verifying that the residue is mainly composed of tin oxide particles. Figure 3 The SEM and EDS analyses revealed that the residue mainly consisted of needle-like, rod-like, and prismatic particles, with Sn and O elements highly co-located, indicating that the residue was primarily composed of tin oxide particles. The results demonstrate that the embodiments of this invention can effectively separate and quantitatively analyze tin in solid solution and tin oxide.
[0039] Example 2 Weigh 11.638 g of Cu-SnO2 composite material sample and dissolve it in 100 mL of 68% nitric acid solution. Immediately add 0.12 times the sample mass of complexing agent citric acid and stir for 5 min for complexation stabilization treatment. Then filter the sample using a 0.10 μm nylon filter membrane and collect the filtrate and filter residue separately.
[0040] The filtrate was diluted to 1000 mL and the tin content was determined by ICP-OES. The calculated tin content in solid solution was 0.0828 wt.%. The filter residue was washed 10 times and dried at 80℃, and the mass of the residue was measured to be 27.60 mg, which was converted to an tin oxide content of 0.1868 wt.%. The actual measured total tin content was 0.2696 wt.%.
[0041] Example 3 Weigh 5.917 g of Cu-SnO2 composite material sample and dissolve it in 100 mL of 50% nitric acid solution. After the sample is completely dissolved, immediately add 0.08 times the sample mass of complexing agent oxalic acid and stir for 10 min for complexation stabilization treatment. Then filter the solution using a 1 μm PTFE membrane and collect the filtrate and filter residue separately.
[0042] The filtrate was diluted to 100 mL and the tin content was determined by ICP-OES. The calculated solid-solid tin content was 0.0993 wt.%. The filter residue was washed five times, dried at 105 °C, and the residue mass was measured to be 8.99 mg, which was converted to an oxide tin content of 0.1197 wt.%. The actual measured total tin content was 0.2190 wt.%.
[0043] Comparative Example 1 To investigate the effect of the complexing agent on the analytical results, the same experimental conditions as in Example 2 were used, but without the complexing agent. After washing and drying, the mass of the filter residue was measured to be 19.76 mg, which corresponds to a tin oxide content of 0.1423 wt.%. The actual measured total tin content was 0.2166 wt.%. Compared to Example 2, the tin oxide content decreased from 0.1868 wt.% to 0.1423 wt.% without the complexing agent, indicating that complexation stabilization treatment is beneficial for improving the stability and reliability of the separation and analysis results of tin in different forms.
[0044] Comparative Example 2 To simulate existing technical conditions, 35.510 g of Cu-SnO2 composite material sample was weighed and dissolved in 100 mL of 68% nitric acid solution without adding a complexing agent. The sample was then filtered using ordinary filter paper with a pore size of approximately 10 μm. All other steps were the same as in Example 1.
[0045] The filtrate, after ICP-OES analysis, showed a dissolved tin content of 0.2028 wt.%. The filter residue, after washing and drying, had a mass of 53.62 mg, which translates to a tin oxide content of 0.1189 wt.%. The actual measured total tin content was 0.3217 wt.%. Figure 4 The SEM results of the residue obtained in Comparative Example 2 showed a large number of irregularly agglomerated particles, and EDS analysis indicated that Sn and O elements were enriched in the agglomerated particles. Compared with the uniformly dispersed needle-shaped, rod-shaped, and prismatic SnO2 particles obtained in Example 1, the residue obtained in Comparative Example 2 had poor dispersibility and a significantly reduced content of tin oxide, indicating that using ordinary filter paper without complexation stabilization treatment is not conducive to the separation and retention of tin oxide particles.
[0046] It should be noted that, where there is no conflict, the features in the embodiments of this application can be combined with each other.
[0047] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for the quantitative analysis of two forms of tin in Cu-SnO2 composite materials, characterized in that, Includes the following steps: After the Cu-SnO2 composite material sample was fully dissolved in acid, a complexing agent was added and stirred. Then, solid-liquid separation was performed using a microporous filter membrane to obtain a filtrate containing tin in solid solution and metal ions dissolved in the solution, as well as a residue containing tin oxide particles. The filtrate was quantitatively analyzed to determine the tin content, and the residue was washed to determine the content of tin oxide. The contents of solid solution tin and tin oxide in Cu-SnO2 composite material were obtained by the above determination.
2. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite material according to claim 1, characterized in that, The complexing agent is at least one of tartaric acid, citric acid, ethylenediaminetetraacetic acid, or oxalic acid, and the amount of complexing agent added is 0.05-0.2 times the mass of the sample.
3. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite material according to claim 1, characterized in that, The complexing agent is tartaric acid, and the amount of the complexing agent added is 0.08-0.12 times the mass of the sample.
4. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite material according to claim 1, characterized in that, The microporous filter membrane is a polyethersulfone filter membrane, a polytetrafluoroethylene filter membrane, or a nylon filter membrane, and the pore size of the microporous filter membrane is 0.10-1.00 μm.
5. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite material according to claim 1, characterized in that, The microporous filter membrane is a polyethersulfone filter membrane with a pore size of 0.22-0.45 μm.
6. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite material according to claim 1, characterized in that, The method for determining the content of tin oxide after cleaning the residue includes: washing 3-10 times, drying at 80-120℃ and recording the mass of the residue, and calculating the content of tin oxide corresponding to the residue based on the mass fraction of tin in the tin oxide.
7. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite material according to claim 1, characterized in that, After determining the content of tin oxide in the residue cleaning process, the method further includes a step of confirming the true composition of the residue, specifically including: The residue was examined using an X-ray diffractometer with a scanning range of 10°-90°. The obtained diffraction peaks were compared with standard cards to confirm the presence of the SnO2 phase in the residue. The morphological characteristics of the residue particles were observed using a scanning electron microscope, and point and surface scanning analyses were performed using energy dispersive spectroscopy to confirm the distribution of Sn and O elements in the particles.
8. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite material according to claim 1, characterized in that, After obtaining the contents of tin in solid solution and tin in oxide in Cu-SnO2 composite material, the method further includes the step of calculating the ratio between tin in oxide and tin in solid solution, thereby establishing a quantitative analysis system for tin elements in different forms in Cu-SnO2 composite material.
9. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite materials according to any one of claims 1-8, characterized in that, The acid used for dissolution is a nitric acid or other acid system with a mass fraction of 50-68% that can dissolve the copper matrix while retaining the tin oxide particles. The mass of the acid added is 3-20 times the mass of the sample.
10. The method for quantitative analysis of two forms of tin in Cu-SnO2 composite materials according to any one of claims 1-8, characterized in that, The acid used for dissolution is a 60% nitric acid solution.
Citation Information
Patent Citations
Copper alloy conductor and method of fabricating the same
CN100347790C
Copper alloy conductor and method of fabricating the same
CN1501409A